Meckel's diverticulum causing acute intestinal obstruction: A case report and comprehensive review of the literature. (June 2022) - Almas, Talal; Alsubai, Abdulla K.; Ahmed, Danyal; Ullah, Muneeb; Murad, Muhammad Faisal; Abdulkarim, Khadeer; Alwheibi, Eissa Sultan; Alansaari, Mohamed; Abdullatif, Tala; Hadeed, Sebastian; Khan, Muhammad Omer; Alsufyani, Majid; et al.
Abstract: Introduction: Meckel's diverticulum is a congenital anomaly that is often detected incidentally. When it presents symptomatically, it causes painless gastrointestinal bleeding. Nevertheless, in rare instances, it can cause acute intestinal obstruction, often obscuring the true clinical picture. Case presentation: A 31-year-old male presented to the emergency department with a 24-h history of unremitting nausea, biliary emesis, abdominal distension, and absolute constipation. After ruling out the most common etiologies of acute bowel obstruction, radiological imaging was obtained and was suggestive of meckel's diverticulum. Laparoscopic meckel's diverticulectomy was performed, with the subsequent histopathological analysis confirming ectopic gastric tissue. Discussion: Meckel's diverticulum occurs consequent to incomplete obliteration of the vitelline or omphalomesenteric duct, which connects the developing intestines to the yolk sac. It is found in roughly 2% of the population, of which only about 4% may become symptomatic due to any number of complications. Specifically, small bowel obstruction (SBO) and diverticulitis secondary to ectopic gastric or pancreatic tissue are the most common presentations of symptomatic MD. Conclusion: Although relatively rare in adults, MD should be considered in the list of differentials in patients with intussusception leading to SBO, especially on a background history unremarkable for the most common etiologies causing SBO including post-operative adhesions and hernias. Highlights: Meckel's diverticulum, a rare congenital abnormality, usually presents with painless bleeding. However, in rare instances, it might cause acute intestinal obstruction, often obscuring the clinical picture. In patients presenting with acute intestinal obstruction on a background history unremarkable for the most common etiologies, meckel's diverticulitis should be considered in the list of differentials. In such instances, meckel's diverticulectomy remains the mainstay of surgical management, yielding a prompt resolution of obstructive symptoms.